The Use of Diagnostic Plots and Interaction Plots for Describing the Effect of Factors Affecting Vanillin Adsorption onto Resin H103 - Rozaimi, Abu Samah; N., Zainol; Phang, Lai Yee; Suraini, Abd Aziz (2017)
Fractional factorial screening methodology was used in order to explain the effect of several factors - contact time, initial vanillin concentration, resin dosage, pH and temperature - affecting the adsorption of vanillin onto resin H103 in batch mode. With the aid of Design Expert, 25 fractional factorial screening was utilized. Statistical analysis showed that initial vanillin concentration and resin dosage were significant. The analysis of variance (ANOVA) gave a very good determination coefficient (R2) of 0.9996. Diagnostic plots, such as normal probability plot, residuals versus predicted values plot, and outlier T plot; and factors interaction plots, were used to further validate the model obtained and to explain the effects of the parameters involved in the adsorption of vanillin onto resin H103.